AN INVESTIGATION OF DUAL FUNCTION HYDRATE INHIBITOR FOR CARBON DIOXIDE-METHANE MIXTURES - KASSIM, ZAMZILA (2020)
The development of ionic liquids as an alternative to thermodynamic and kinetic hydrate inhibitor has been a subject of interest due to its unlimited cation and anion pairing, high vapour pressure, and thermal stability. However, the ammonium-based ionic liquid influence is still not fully understood. Hence, this work investigates the influence of tetraethyl ammonium chloride (TEACl) as a dual function (thermodynamic and kinetic) hydrate inhibitor on CO2, CH4 and binary gas mixtures of CO2-CH4 (30-70 and 70-30). The COSMO-RS evaluates the characteristics of TEACl such as hydrogen bond strength and electronegativity for dual function hydrate inhibitor. TEACl influence in the gas hydrate systems was evaluated using a high-pressure Sapphire cell set-up.